The Semantic Characteristic of the Concepts "Good and Evil" in German and Uzbek Languages (Zien Journal of Social Sciences and Humanities, 2022)
This article covers the interpretation of the concepts "good" and "evil" in German and Uzbek on the basis of the opinions of scientists. The semantic features of this concept are explained with examples in both languages